Dùng hằng đẳng thức để khai triển và thu gọn: $(3a-1)^{2}$ $+2(9a^{2}$ $-1)+(3a+1)^{2}$

Question

Dùng hằng đẳng thức để khai triển và thu gọn:
$(3a-1)^{2}$ $+2(9a^{2}$ $-1)+(3a+1)^{2}$

in progress 0
Sadie 3 tuần 2021-07-06T09:39:36+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-07-06T09:41:04+00:00

    $\begin{array}{l}(3a – 1)^2 + 2(9a^2 – 1) + (3a + 1)^2\\ = (3a – 1)^2 +2.(3a-1)(3a + 1) + (3a + 1)^2\\ = [(3a -1) + (3a + 1)]^2\\ = (6a)^2\\= 36a^2\end{array}$

    0
    2021-07-06T09:41:06+00:00

    Đáp án:

    $36a^2$

    Giải thích các bước giải:

    $\begin{array}{l}(3a – 1)^2 + 2(9a^2 – 1) + (3a + 1)^2\\ = (3a – 1)^2 +2.(3a-1)(3a + 1) + (3a + 1)^2\\ = [(3a -1) + (3a + 1)]^2\\ = (6a)^2\\= 36a^2\end{array}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )